Scutellarin regulates microglia-mediated TNC1 astrocytic reaction and astrogliosis in cerebral ischemia in the adult rats. Issue 1 (December 2015) - Fang, Ming; Yuan, Yun; Rangarajan, Parakalan; Lu, Jia; Wu, Yajun; Wang, Huadong; Wu, Chunyun; Ling, Eng-Ang
Abstract Background Scutellarin, an anti-inflammatory agent, effectively suppressed microglia activation in rats with middle cerebral artery occlusion (MCAO). Robust microglia activation, acute in onset, was followed by astrogliosis. This study was aimed to determine if scutellarin would also affect the reactive astrocytes that play an important role in tissue repair. Expression of GFAP and Notch-1 and its members: Notch receptor intracellular domain (NICD), and transcription factor hairy and enhancer of split-1 (HES-1), together with nestin and proinflammatory mediators was assessed by immunofluorescence staining in TNC1 astrocytes treated, respectively, with BV-2 conditioned medium (CM) and CM + lipopolysaccharide (LPS) (CM + L) serving as the controls, and conditioned medium derived from LPS-activated BV-2 cells pretreated with scutellarin (CM + SL). Study of the above biomarkers was then extended to reactive astrocytes in scutellarin injected MCAO rats. Results TNC1 astrocytes remained relatively unreactive in terms of expression of different biomarkers to direct scutellarin treatment when compared with the control cells. In comparison to cells in the control medium (CM, CM + L), they responded vigorously to CM + SL as evidenced by the enhanced protein expression of GFAP, Notch-1, NICD and HES-1 coupled with that of nestin, TNF-α, IL-1β, and iNOS by Western and immunofluorescence analysis. Electron microscopy showed marked hypertrophy and cell expansion of TNC1 astrocytes bearing many filamentous processes indicative of enhanced astrocyte reaction when treated with CM + SL. In MCAO rats, scutellarin also augmented the expression of the above markers in reactive astrocytes; moreover, astrocytes were evidently hypertrophic. Conclusions The results suggest that scutellarin regulates astrogliosis; more importantly, it is microglia-mediated as demonstrated in vitro. Increased expression of Notch signaling in synchrony with nestin may be linked to proliferation and "de-differentiation" of reactive astrocytes; the significance of enhanced TNF-α, IL-1β and iNOS expression in reactive astrocytes by scutellarin may be neuroprotective but this remains speculative.